2022
DOI: 10.3390/molecules27092878
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methyl Jasmonate and Nano-Methyl Jasmonate Treatments on Monastrell Wine Volatile Composition

Abstract: The application of methyl jasmonate (MeJ) as an elicitor to enhance secondary metabolites in grapes and wines has been studied, but there is little information about its use in conjunction with nanotechnology and no information about its effects on wine volatile compounds. This led us to study the impact of nanoparticles doped with MeJ (Nano-MeJ, 1mM MeJ) on the volatile composition of Monastrell wines over three seasons, compared with the application of MeJ in a conventional way (10 mM MeJ). The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The study was performed over three seasons (2019–2021) in the experimental field El Chaparral located in Cehegin (Murcia, Spain) (latitude 38.11179 and longitude −1.6808), where the climatic conditions are considered semi-arid continental and the soil is loamy sand. The vineyards were Vitis vinifera L. Monastrell variety on Richter 110 rootstock, trained in a bilateral cordon system and within-row spacing of 3 × 0.8 m. Three treatments were applied in triplicate at veraison and one week later, following the same protocol described above [ 24 ], with 10 vines per replicate: (i) control (water), (ii) 10 mM MeJ and (iii) nano-MeJ at 3.6 g L −1 (equivalent to 1 mM in MeJ). When the grapes reached technological maturity (sugar/acidity ratio), a manual harvest was carried out.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was performed over three seasons (2019–2021) in the experimental field El Chaparral located in Cehegin (Murcia, Spain) (latitude 38.11179 and longitude −1.6808), where the climatic conditions are considered semi-arid continental and the soil is loamy sand. The vineyards were Vitis vinifera L. Monastrell variety on Richter 110 rootstock, trained in a bilateral cordon system and within-row spacing of 3 × 0.8 m. Three treatments were applied in triplicate at veraison and one week later, following the same protocol described above [ 24 ], with 10 vines per replicate: (i) control (water), (ii) 10 mM MeJ and (iii) nano-MeJ at 3.6 g L −1 (equivalent to 1 mM in MeJ). When the grapes reached technological maturity (sugar/acidity ratio), a manual harvest was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, other researchers showed an increase in stilbene content in Monastrell wines from grapes treated with MeJ and nano-MeJ [ 23 ]. Finally, Giménez-Bañón et al [ 24 ] found a higher concentration of fruity ester compounds in Monastrell wines from nano-MeJ-treated grapes.…”
Section: Introductionmentioning
confidence: 99%
“…The extract was dried under vacuum at 35 °C with a Centrivap concentrator (Labconco, Kansas City, MO, USA) and subsequently redissolved in 2 mL methanol (MeOH) (gradient highperformance liquid chromatography; PAI-ACS, Panreac). The methanolic extract was left to react with the phloroglucinolysis reagent (1:1) in a water bath (20 2) with a flow rate of 0.8 mL min −1 was used for separation. Eluted peaks were monitored at 280 nm.…”
Section: Determination Of Pas From Skins and Seeds By High-performanc...mentioning
confidence: 99%
“…12 There are numerous studies on the effect of the application of elicitors in the field, specifically in the vineyard; two examples of such compounds are methyl jasmonate (MeJ) and benzothiadiazole (BTH; benzo-(1,2,3)-thiadiazole-7-carbothioic acid S-methyl ester), which are effective in increasing concentration of aromas, nitrogen compounds, and phenolic compounds in different varieties of wine grapes. [15][16][17][18][19][20] MeJ has been mainly implicated as a mediator in plant responses triggered by wounding and insect feeding and is involved in pathogen resistance. 21 BTH is a synthetic functional analogue of the plant endogenous hormone-like compound salicylic acid, which induces defence genes leading to systemic acquired resistance and an increase in phenolic production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation